The Future Isn’t What It Used to Be: Heterotopia, Power, and Surveillance in Caryl Churchill’s Far Away - Mhayyal, Basaad; ALGhareeb , Sanaa (Al-Adab Journal, 2024)
This paper aims to answer the question of whether dystopian narratives may have any glimpse of hope although they reflect a pessimistic view of their writers. In Far Away, Caryl Churchill’s most terrifying play despite not including horror scenes except for the parade scene that takes place every night and the terror is reflected through conversation only, the playwright tried her best to shed light on a grotesque vision of a dystopian society where only terrorism, oppression, imprisonment, disloyalty, and violence are found. This dystopian world reveals how everything is considered an enemy to everything else, even nature becomes an enemy to humans and Churchill humanizes nature instead of dehumanizing people. This paper tackles Far Away in the light of the Foucauldian concepts of the docile body, heterotopia, carceral society, power, and surveillance which are reflected by Churchill.